(untitled) (Research, Society and Development, 2022)
The wood from native forests became, over the years, a scarce and highly valued material, precisely because of the difficulty of obtaining it by legal means, thus avoiding deforestation. As a sustainable alternative, the development of reforestation for industrial purposes, especially of Eucalyptus species, stands out. The objective of this paper is to present the role of forestry and eucalyptus cultivation as an economic activity, considering social aspects. The information from this work may provide subsidies to policy makers and development agendas of the region, leveraging the eucalyptus plantations and taking into consideration the environmental, social, and economic aspects. The surveys carried out identified the benefits generated in economic, social, and environmental development that the planted forest sector can offer to the regions where it is established. Considering the three aspects, we highlight the indicators of income generation and direct and indirect jobs, soil and water conservation, the capture of greenhouse gases, and the conservation and preservation of native forests.